Reduction Kinetics Of Manganese Oxide From HC FeMn Slags - G. Tranell; S. Gaal; D. Lu; M. Tangstad; J. Safarian (The Southern African Institute of Mining and Metallurgy, 2007)
The kinetics of MnO reduction from high carbon ferromanganese slag was investigated using a sessile drop technique at 1600 ºC. The effects of reductant type, ambient atmosphere and slag composition on the MnO reduction were illuminated. Two different types of industrial reductants (ground to a particle size of 44 to 106micron and pressed to pellets) were used as substrates for small slag droplets of varying composition, which were reacted in a CO or Ar atmosphere with the reaction studied in-situ. The cross sections of the reacted slag-carbon samples were subsequently studied by EPMA to find the extent of MnO reduction as a function of reaction time. It was found that the rate of MnO reduction is affected by both the type of reductant, the ambient atmosphere and the presence of metallic components in the slag. Higher reduction rates were obtained for charcoal than for coke as reductant while a CO atmosphere unexpectedly yielded faster MnO reduction than an Ar atmosphere. It was also found that metal prills in the initial slag will increase the rate ofMnO reduction.